Impact of Natalizumab on Ambulatory Improvement in Secondary Progressive and Disabled Relapsing-Remitting Multiple Sclerosis - Cadavid, Diego; Jurgensen, Stephanie; Lee, Sophia (PloS one, 2013)
There is an unmet need for disease-modifying therapies to improve ambulatory function in disabled subjects with multiple sclerosis. Assess the effects of natalizumab on ambulatory function in disabled subjects with relapsing-remitting multiple sclerosis (RRMS) or secondary progressive multiple sclerosis (SPMS). We retrospectively reviewed ambulatory function as measured by timed 25-foot walk (T25FW) in clinical trial subjects with an Expanded Disability Status Scale score ≥3.5, including RRMS subjects from the phase 3 AFFIRM and SENTINEL trials, relapsing SPMS subjects from the phase 2 MS231 study, and nonrelapsing SPMS subjects from the phase 1b DELIVER study. For comparison, SPMS subjects from the intramuscular interferon beta-1a (IM IFNβ-1a) IMPACT study were also analyzed. Improvement in ambulation was measured using T25FW responder status; response was defined as faster walking times over shorter (6-9-month) or longer (24-30-month) treatment periods relative to subjects' best predose walking times. There were two to four times more T25FW responders among disabled MS subjects in the natalizumab arms than in the placebo or IM IFNβ-1a arms. Responders walked 25 feet an average of 24%-45% faster than nonresponders. Natalizumab improves ambulatory function in disabled RRMS subjects and may have efficacy in disabled SPMS subjects. Confirmation of the latter finding in a prospective SPMS study is warranted.